2023
DOI: 10.1007/s13592-022-00985-8
|View full text |Cite
|
Sign up to set email alerts
|

The significance of Apis cerana cerana (Hymenoptera: Apidae) gnawing off the old brood cells

Abstract: Apis cerana cerana has the biological characteristic of gnawing off the old brood cells which reared multiple generations of workers. This study investigated the internal structure of newly built, old, and semi-rebuilt brood cells and their effects on the morphological development of workers to understand the significance of Apis cerana cerana gnawing off the old brood cells. The results showed that there was no significant difference among the three diameters (at the top, middle, and bottom positions) of newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…A study examining the brood cell structure of Western honey bees ( A. mellifera ) reported that workers expand the volume of brood cells by carefully cleaning the accumulated debris within the cells and secreting wax to increase the cell wall height, which helps the normal development of broods ( Таранов 1961 ). In contrast, A. c. cerana has evolved biological traits to gnaw away old combs, balancing the negative impact of old brood cells on the colony ( Meng et al 2023 ). In this study, we observed that age is one of the major factors contributing to the comb-gnawing behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study examining the brood cell structure of Western honey bees ( A. mellifera ) reported that workers expand the volume of brood cells by carefully cleaning the accumulated debris within the cells and secreting wax to increase the cell wall height, which helps the normal development of broods ( Таранов 1961 ). In contrast, A. c. cerana has evolved biological traits to gnaw away old combs, balancing the negative impact of old brood cells on the colony ( Meng et al 2023 ). In this study, we observed that age is one of the major factors contributing to the comb-gnawing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Esters and hydrocarbons are the primary components of beeswax that can absorb dark pigments that are produced from the brood’s secretions, turning the comb color brown or black, and the comb color intensity is typically associated with its age ( Tulloch 1980 , Berry and Delaplane 2001 ). After multiple generations of worker rearing, a brood cell becomes reduced in size due to the accumulation of cocoons and other materials ( Hepburn et al 2007 , Meng et al 2023 ). The reduced size of brood cells negatively impacts the morphological characteristics of workers ( Alfalah et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, two types of experimental combs were collected. These included three single-generation combs that had reared one generation of workers and three multi-generation combs that had reared numerous generations of workers (approximately eight generations), with a 1-year age and with some brood cells gnawed by workers [ 11 , 39 ]. Then, a 50 cm 2 comb block was cut from each comb’s brood-rearing area using an uncapping knife.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, old combs produce a positive feedback regulation that leads to several negative effects on the colony [ 8 , 9 ]. Compared to newly built or fresh combs, the structure of old brood cells is altered, leading to a volume reduction of about 9% [ 10 , 11 ]. This results in workers with lighter birth weights and reduced external morphometric sizes [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation